DIALECTICS OF RELEVANCE: THE CHALLENGE OF PURIFICATION IN MUHAMMADIYAH FROM THE PERSPECTIVE OF PROPHETIC AND TRANDSCENDENTAL-BASED LAW (PROGRESSIVE AND CONSERVATIVE VIEWS) - Noor Rahmad; Absori; Eren Arif Budiman (Bengkoelen Justice : Jurnal Ilmu Hukum, 2024)
Understanding the concept of purification or spiritual cleansing plays an important role in many religious traditions, including Muhammadiyah. Muhammadiyah, as an Islamic organization that promotes moderate national and Islamic values, has long dedicated itself to understanding religious concepts in the context of the times. However, in the process of adapting to the changing times, there are often different views, both in progressive and conservative approaches, in interpreting and applying religious concepts, including purification. Based on the research findings, the study can generate concrete policy recommendations and strategies to promote inclusive and progressive purification of religious understanding in Muhammadiyah, as well as ways to facilitate dialog and respectful understanding between progressive and conservative views.This research aims to explore the relevance of the concept of purification among Muhammadiyah and identify the main challenges that arise when the concept is interpreted through progressive and conservative views. By understanding the different views, it is hoped that this research can provide a deeper insight into the concept of purification in the context of Muhammadiyah, as well as its implications in religious practice. The approach chosen in this research is to analyze the thoughts, opinions, and interpretations of scholars and key figures from both views, as well as empirical data from among Muhammadiyah citizens. This research is expected to make a significant contribution in expanding the understanding of religious thought in Muhammadiyah and the relevance of the concept of purification in the context of differences in progressive and conservative views. This research aims to analyze the dialectic of purification understanding among Muhammadiyah, between progressive and conservative views. This research examines the relationship between the normative side of the Qur'an and the understanding side, as well as how Muhammadiyah tries to purify religion from shirk, heresy, and khurafat through rationalization and spiritualization of sharia. Based on the research findings, the study can produce concrete policy recommendations and strategies to promote the purification of inclusive and progressive religious understanding in Muhammadiyah, as well as ways to facilitate dialogue and respectful understanding between progressive and conservative views. Keywords: Purification, Conservative Progressive.